Assessing the soil physical characteristics of the gallery woods area at the hydrographic Mariana sub-catchment for environmental conservation - Camargo, M. F. (2013)
The objective of this work was to characterize soil physical properties of the gallery woods area at the hydrographic Mariana sub-catchment. The physical attributes evaluated were: bulk density, gravimetric humidity, soil porosity and mechanical resistance to penetration. The field work was carried out at Alta Floresta-MT, Brazil. Nine plots of 20 m × 50 m in surface were marked along the upper and middle river course areas in such a way that they were representative of all the sub-catchment extension. The experimental design was completely randomized. Soil density of the gallery woods area was higher than that of the native forest, so that development of the root system of the trees even could be restricted. Gravimetric humidity was found to be homogeneous when different areas or different depths were compared. Soil porosity was found to be adequate for native gallery woods. Mean penetration resistance at the 0-0.25 m depth was classified as moderate, bout hint the upper and middle river course areas.